The association between patients' preferred treatment after the use of a patient decision aid and their choice of eventual treatment - Carmen S. S. Latenstein; Floris M. Thunnissen; Bastiaan J. M. Thomeer; Bob J. vanWely; Marjan J. Meinders; Glyn Elwyn; Philip R. deReuver (Wiley, 2020)
Abstract Objective To investigate the association between patients' preferred treatment and eventual treatment. Second, to compare patients with surgical treatment to watchful waiting in order to identify predictive factors for surgery. Methods A single‐centre retrospective study was performed between December 2015 and August 2018. Patients (≥18 years) who used a patient decision aid (PDA) for gallstones or inguinal hernia were included. After their first surgical consultation, patients received access to an online PDA. The patients' preferred treatment after the PDA was compared with their choice of eventual treatment. Multivariable regression analyses were performed for predictive factors for surgery. Results In total, 567 patients with gallstones and 585 patients with an inguinal hernia were included. Of the patients with gallstones, 121 (21%) preferred watchful waiting, 367 (65%) preferred surgery, and 79 (14%) were not sure. The patients' preferred treatment was performed in 85.9%. Frequent pain attacks (OR 2.1, 95% CI 1.1‐3.9, P = .020) and preference for surgery (OR 4.4, 95% CI 1.9‐10.1, P = .001) independently predicted surgery. Of the patients with an inguinal hernia, 77 (13.2%) preferred watchful waiting, 452 (78.8%) preferred surgery, and 56 (9.6%) were not sure. The patients' preferred treatment was performed in 86.0%. The preference for surgery (OR 5.2, 95% CI 2.5‐10.6, P < .001) independently predicted surgery and worry about complications predicted avoidance of surgery (OR 0.5, 95% CI 0.2‐1.0, P = .037). Conclusion This study, reflecting current clinical care, shows that patients' preferred treatment after using a PDA matches their eventual treatment choice in 86% of patients with gallstones or an inguinal hernia. In these patients, symptoms and patients' preference for surgery independently predicts eventual choice of surgery.